1967
DOI: 10.1037/h0024713
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for the use of verbal associations.

Abstract: STUDIES OF CONTEXTUAL EFFECTS ON RESPONSES OBTAINED TO STIMULI IN WORD ASSOCIATION TESTS ARE REVIEWED UNDER THE HEADINGS DIRECT PRIMING, INDIRECT PRIMING, AND STIMULUS COMPOUNDING, WITH ATTENTION TO BOTH POSITIVE AND NEGATIVE RESULTS, AND AN ATTEMPT IS MADE TO SUMMARIZE WHAT IS KNOWN ABOUT THE CONDITIONS ASSOCIATED WITH POSITIVE AND WITH NEGATIVE RESULTS. A SUGGESTION IS TENTATIVELY MADE THAT IF ITEMS BELONG WITHIN THE SAME ASSOCIATIVE STRUCTURE, PRIMING OF AN ITEM AS A RESPONSE TO ANOTHER ITEM MAY OCCUR; WHER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0
4

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 18 publications
0
52
0
4
Order By: Relevance
“…A growing number of recent studies have demonstrated, however, that memory can also be indexed by facilitated performance on tests that do not require intentional recollection, such as word completion (e.g., Graf, Squire, & Mandler, 1984;Warrington & Weiskrantz, 1968, 1974, free association (e.g., Shimamura & Squire, 1984;Storms, 1958), word identification (e.g., Clarke & Morton, 1983;Jacoby & Dallas, 1981), and lexical decision (e.g., Meyer & Schvaneveldt, 1971;Scarborough, Gerard, & Cortese, 1979). The latter facilitations are generally known as directpriming effeets (e.g., Cofer, 1967). The descriptive terms implicit and explicithave been used to distinguish between the effects of memory episodes that are revealed by performance on priming tests on the one hand and by performance on recall and recognition tests on the other hand (Graf & Schacter, 1985;Schacter & Graf, 1986).…”
mentioning
confidence: 99%
“…A growing number of recent studies have demonstrated, however, that memory can also be indexed by facilitated performance on tests that do not require intentional recollection, such as word completion (e.g., Graf, Squire, & Mandler, 1984;Warrington & Weiskrantz, 1968, 1974, free association (e.g., Shimamura & Squire, 1984;Storms, 1958), word identification (e.g., Clarke & Morton, 1983;Jacoby & Dallas, 1981), and lexical decision (e.g., Meyer & Schvaneveldt, 1971;Scarborough, Gerard, & Cortese, 1979). The latter facilitations are generally known as directpriming effeets (e.g., Cofer, 1967). The descriptive terms implicit and explicithave been used to distinguish between the effects of memory episodes that are revealed by performance on priming tests on the one hand and by performance on recall and recognition tests on the other hand (Graf & Schacter, 1985;Schacter & Graf, 1986).…”
mentioning
confidence: 99%
“…This facilitation of test performance has been labeled repetition or direct priming (cf. Cofer, 1967), and it occurs without deliberate intent to recollect the past episode. Graf and Schacter (1985) have used the descriptive terms explicit and implicit to describe the forms of memory involved in recall/recognition and priming performance, respectively.…”
mentioning
confidence: 99%
“…If we look at the word-association test employed in that study as a repeated test of implicit conceptual memory (Roediger, 1990), one can conceive that at least some of the responses to the homograph organ following piano are associates to piano that occurred either explicitly (the response) or implicitly (other words that came to mind when piano was presented). It is a well-established finding that explicit prestudy of potential associates can lead to their production as responses in a word-association task (see Cofer, 1967, for a review of what he labeled direct priming). If an implicit form of direct priming occurs in this case, then on second occurrence, when organ is preceded by liver, there might be competition between associations to liver and organ and the earlier associations to piano and organ.…”
Section: Notesmentioning
confidence: 99%